Marriage breakup reasons of divorced applicant Couples - Mohsenzadeh, Farshad; Nazari, Ali Mohammad (International Journal of Education and Cognitive Sciences, 2022)
Introduction: The aim of the present research was to examine the reasons for marriage breakup from the perspective of the couples who were applicants for divorce. Materials and methods: The sample consisted of 28 couples, who were applicants for divorce in the Judiciary House of Kermanshah. Participants were recruited through purposeful criterion sampling procedures and interviewed accordingly. Couples who met criterions include at least, 2 years of marriage, experiencing chronic and severe conflict and the reason of applying for divorce must not be acute psycho-physiological complications or special disabilities which make the continuation of marital life difficult.Results: The data in this research were collected through conducting in-depth interviews with couples, one member of which was applicants for divorce. The reasons for marriage failure among the research sample include Premarital Factors like Marriage with Improper Motive, escaping from social pressures and unpleasant atmosphere of paternal house and coerced wedding and Post-marriage factors encompass, Little presence of husband at home and the continuation of celibacy bonds ,Non-separation from the family of origin, Non-separation from the family of origin, Gender role conflicts, Lack of sexual attraction, violence, infidelity, Suspicion, Financial problems, Addiction.Conclusion: Theoretical and research localization and designing interventions on the basis of contextual knowledge are important suggestions and at the same time challenging that can be deduced from the findings of the present research